Advances in mitochondria-centered mechanism behind the roles of androgens and androgen receptor in the regulation of glucose and lipid metabolism - Yin, Lijun; Qi, Shuo; Zhu, Zhiqiang (Frontiers in Endocrinology, 2023)
An increasing number of studies have reported that androgens and androgen receptors (AR) play important roles in the regulation of glucose and lipid metabolism. Impaired glucose and lipid metabolism and the development of obesity-related diseases have been found in either hypogonadal men or male rodents with androgen deficiency. Exogenous androgens supplementation can effectively improve these disorders, but the mechanism by which androgens regulate glucose and lipid metabolism has not been fully elucidated. Mitochondria, as powerhouses within cells, are key organelles influencing glucose and lipid metabolism. Evidence from both pre-clinical and clinical studies has reported that the regulation of glucose and lipid metabolism by androgens/AR is strongly associated with the impact on the content and function of mitochondria, but few studies have systematically reported the regulatory effect and the molecular mechanism. In this paper, we review the effect of androgens/AR on mitochondrial content, morphology, quality control system, and function, with emphases on molecular mechanisms. Additionally, we discuss the sex-dimorphic effect of androgens on mitochondria. This paper provides a theoretical basis for shedding light on the influence and mechanism of androgens on glucose and lipid metabolism and highlights the mitochondria-based explanation for the sex-dimorphic effect of androgens on glucose and lipid metabolism.